A Review of Artistic Research and Literature, Edited by Corina Caduff and Tan Wälchli - Mader, Rachel (Art/Research International)

(untitled) (University of Alberta, 2021)
The intersection between artistic research and literature has so far found little attention in the literature of arts research (Caduff & Wälchli, 2019). This is surprising as artistic research regularly encompasses creative forms of language, but also because creative writing has established itself as an academic discipline for quite some time. The anthology I review here, Artistic Research and Literature, edited by Corina Caduff and Tan Wälchli offers a heterogeneous and hybrid collection of contributions engaged with the performative quality of the research, the definition of the subject, institutional affiliations and self-positionings as well as a diverse range of case studies.